2020
DOI: 10.3389/fphar.2020.550205
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Generic Sofosbuvir Plus Daclatasvir and Sofosbuvir/Velpatasvir in HCV Genotype 3-Infected Patients: Real-World Outcomes From Pakistan

Abstract: Background Direct-acting antivirals (DAAs) therapeutic regimens are highly effective against chronic hepatitis C virus (HCV) infection. However, HCV patients with genotype 3 (GT3) respond in a suboptimal way. This study aims to identify which of the DAAs-based therapeutic regimens are the best option for GT3. Methods Multiple governments and private tertiary care hospitals were involved in this real-life study of HCV-GT3 patients treated with DAAs. The efficacy and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 44 publications
7
15
0
Order By: Relevance
“…Similarly, in a prospective observational study conducted in Pakistan in which 1,388 patients with chronic HCV were enrolled, and 30% of these patients received sofosbuvir and velpatasvir, the overall SVR rates for the cohort who received sofosbuvir and velpatasvir was 94.7, while in patients with cirrhosis, it was 88%. The findings of this study are in agreement with our study [ 12 ]. Our study showed relatively low SVR rates in patients with cirrhosis, 89.7% compared to 98.3% in non-cirrhotic chronic hepatitis C patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, in a prospective observational study conducted in Pakistan in which 1,388 patients with chronic HCV were enrolled, and 30% of these patients received sofosbuvir and velpatasvir, the overall SVR rates for the cohort who received sofosbuvir and velpatasvir was 94.7, while in patients with cirrhosis, it was 88%. The findings of this study are in agreement with our study [ 12 ]. Our study showed relatively low SVR rates in patients with cirrhosis, 89.7% compared to 98.3% in non-cirrhotic chronic hepatitis C patients.…”
Section: Discussionsupporting
confidence: 94%
“…Our study showed relatively low SVR rates in patients with cirrhosis, 89.7% compared to 98.3% in non-cirrhotic chronic hepatitis C patients. Similar trends have been observed in other studies [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Mangia et al documented a 90.5% cure rate with SOF/VEL + RBV regimen in the RWE population, but only ten GT3 infected patients with liver cirrhosis were included [ 22 ]. The efficacy of 88% was demonstrated in a real-life population consisted of 34 patients, including 31 treatment-experienced with both IFN- and DAA-based except NS5A-containing regimens [ 23 ]. The much more numerous RWE cohort comprising 267 cirrhotic American Veterans treated with SOF/VEL + RBV analyzed by Belperio et al, including NS5A-experienced individuals, responded in 84.5% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three SOF-based treatments not only had SVR > 90% but their effects were equally fast in a series of patients with advanced fibrosis or cirrhosis[ 90 ]. Even low-priced generic DAAs were both clinically effective and cost-effective[ 91 , 92 ]. Similar efficacy between SOF/DCV and SOF/VEL in genotypes 2 and 3 was also reported in a real world study[ 93 ].…”
Section: Can We Eradicate Hcv By 2030 With Daas Treatment?mentioning
confidence: 99%